A Wastewater Strength Indicator for Estimating the Energy Performance and Recovery Potential in WWTPs - Borisov, Boyan; Ribarova, Irina; Valchev, Dobril; Radovanov, Viden; Lazarova, Svetlana; Kostova, Irina (Salehan Institute of Higher Education, 2026)
This study aims to propose a practical indicator that enables quick and reliable evaluation of the relationship between influent characteristics and energy performance and recovery in municipal wastewater treatment plants (WWTPs). A composite Wastewater Strength Indicator (WWSI) was developed, integrating wastewater dilution and pollutant load into a single metric. Theoretical correlations were established through mathematical estimation and verified using case studies of six WWTPs in Bulgaria based on operational data from 2020–2022. WWSI correlates strongly with both specific energy consumption (kWh/kg COD removed) and electrical energy recovery rate. WWTPs with a WWSI below 0.25 perform unsatisfactory, exhibiting specific energy consumption levels above 2.0 kWh/kg removed COD, whereas those with a WWSI above 0.35 demonstrate higher energy efficiency, with specific consumption below 1.0 kWh/kg removed COD. The treatment of low-strength wastewater leads to inherent energy inefficiencies that are difficult to overcome through sludge digestion and cogeneration alone. Despite sludge calorific values ranging from 11.5 to 19.4 MJ/kg, the energy recovery potential in the studied WWTPs remained below 35%, confirming that energy neutrality is challenging for diluted wastewater. A conversion coefficient of 0.039 kWh/MJ was introduced to facilitate rapid estimation of potential electrical recovery from sludge calorific values. The proposed WWSI provides a simple yet effective tool for benchmarking WWTPs and supports future upgrades toward energy-neutral wastewater management.